Development of Andragogy-Based ESP Training through Music Implementation for Rajawali Health Vocational School Alumni - Muhammad Naufal Hilmy; Ansori Ansori; Nandang Rukanda (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
The globalization of the healthcare sector has not only created cross-border employment opportunities but also highlighted the gap between graduates who are ready to compete and those limited by insufficient supporting competencies. One of the major challenges faced by vocational health school alumni is the mastery of English for Specific Purposes (ESP), particularly speaking and listening skills that are essential for clinical communication. In response to this issue, this study aims to develop a communicative and contextual ESP training model for alumni of Rajawali Vocational Health School by integrating andragogical principles and music as a learning medium. This study employed a Participatory Action Research (PAR) approach conducted over a two-month period involving 17 alumni from the Nursing and Pharmacy programs. Through collaborative cycles of planning, action, observation, and reflection, participants were not merely positioned as training subjects but also as active partners in the development of the program. The findings revealed that the developed training model had a significant impact on improving participants’ oral English competencies. Approximately 90% of participants demonstrated meaningful improvement, while 88% achieved the targeted minimum 20% increase in pronunciation and vocabulary assessments. Furthermore, 95% of participants showed high levels of participation and enthusiasm throughout the music-based learning activities. These findings indicate that the integration of andragogical principles and music in ESP training is not only quantitatively effective but also capable of creating relevant, participatory, and sustainable learning experiences for health vocational alumni in responding to the demands of the global workforce.